Development of an intervention to manage knee osteoarthritis risk and symptoms following anterior cruciate ligament injury. Issue 12 (December 2021) - Davis, A.M.; Wong, R.; Steinhart, K.; Cruz, L.; Cudmore, D.; Dwyer, T.; Li, L.; Marks, P.; McGlasson, R.; Urquhart, N.; Wilson, J.A.; Nimmon, L.; et al.
Summary: Introduction: Anterior cruciate ligament (ACL) injury is a risk factor for developing knee osteoarthritis (OA). We developed an intervention to support people manage risk factors for OA. Methods: We conducted one-on-one interviews with 20 individuals with OA symptoms 6–15 years post ACL injury and used a nominal group process during a workshop with 40 patients and healthcare professionals (HCPs) to elicit information on the intervention content and delivery characteristics (timing, HCPs, and methods). Interview data were analyzed using content analysis. Nominal group ideas with importance ratings ≥5 of 7 met criteria for inclusion. Results were integrated, considering similarities and differences. Results: Eight content categories were identified: 1. understanding knee injury and expectations about recovery; 2. understanding OA risk; 3. understanding OA signs and symptoms; 4. managing OA risk; 5. managing knee OA symptoms; 6. information for influencers; 7. credible sources; and, 8. updates on new evidence and treatments. Delivery timing reflected a lifespan approach from time of injury through symptomatic knee OA management. Although multiple media for delivery were identified, introductory face-to-face discussions and opportunity for re-accessing HCPs were critical. All HCPs who treat people with ACL should be familiar with and able to deliver the intervention. Conclusions: This co-development approach identified that an intervention to support people with ACL injury to limit and manage knee OA requires content embedded within an easily accessible, multi-media delivery model with capacity for check-back with HCPs that is appealing to different age groups and personal preferences over the lifespan post injury.